RUNX‐mediated growth arrest and senescence are attenuated by diverse mechanisms in cells expressing RUNX1 fusion oncoproteins. Issue 3 (20th November 2017) - Anderson, Gail; Mackay, Nancy; Gilroy, Kathryn; Hay, Jodie; Borland, Gillian; McDonald, Alma; Bell, Margaret; Hassanudin, Siti Ayuni; Cameron, Ewan; Neil, James C.; Kilbey, Anna
Abstract: RUNX gene over‐expression inhibits growth of primary cells but transforms cells with tumor suppressor defects, consistent with reported associations with tumor progression. In contrast, chromosomal translocations involving RUNX1 are detectable in utero, suggesting an initiating role in leukemias. How do cells expressing RUNX1 fusion oncoproteins evade RUNX‐mediated growth suppression? Previous studies showed that the TEL‐RUNX1 fusion from t(12;21) B‐ALLs is unable to induce senescence‐like growth arrest (SLGA) in primary fibroblasts while potent activity is displayed by the RUNX1‐ETO fusion found in t(8;21) AMLs. We now show that SLGA potential is suppressed in TEL‐RUNX1 but reactivated by deletion of the TEL HLH domain or mutation of a key residue (K99R). Attenuation of SLGA activity is also a feature of RUNX1‐ETO9a, a minor product of t(8;21) translocations with increased leukemogenicity. Finally, while RUNX1‐ETO induces SLGA it also drives a potent senescence‐associated secretory phenotype (SASP), and promotes the immortalization of rare cells that escape SLGA. Moreover, the RUNX1‐ETO SASP is not strictly linked to growth arrest as it is largely suppressed by RUNX1 and partially activated by RUNX1‐ETO9a. These findings underline the heterogeneous nature of premature senescence and the multiple mechanisms by which this failsafe process is subverted in cells expressing RUNX1 oncoproteins. Abstract : This study reveals the diverse mechanisms by which primary cells expressing RUNX1 fusion oncoproteins evade the negative growth consequences of over‐expressed RUNX. Growth arrest activity is markedly attenuated in two fusion derivatives (TEL‐RUNX1 and RUNX1‐ETO9a) but not in RUNX1‐ETO where it is instead antagonized by secretion of pro‐oncogenic cytokines. These studies help to account for the markedly different biology and cell‐type specificity of the RUNX1 oncoproteins.